PENGEMBANGAN VIDEO PEMBELAJARAN MATERI PRA AKSARA MATA PELAJARAN SEJARAH KELAS X SMA NEGERI 9 KOTA JAMBI - Octavianti, Selly (Universitas Batanghari Jambi, 2020)
AbstractThis study aims to produce instructional media products, namely instructional videos and apply them to class X history learning at SMA Negeri 9 Jambi City. The method used in this research is ADDIE which has five stages, namely; 1. Analysis (Analyze), 2. Design (Design), 3. Development (Devolepment), 4. Implementation (Implementation), and 5. Evaluation (Evaluation). The research was conducted at SMA Negeri 9 Jambi City with the research subjects of class X IPA students, amounting to 3 people for individual trials, 8 people for small group trials, and 20 people for large group trials. The results of the first stage of validation by media experts obtained a value of 58.09%, the assessment after revision was obtained a value of 92%. So this product is in the